PATRONASE DAN KLIENTALISME POLITIK (Studi Pada Masyarakat Daerah Pemilihan I, Kabupaten Bangka di Pemilihan Legislatif 2019) - Irfandi Setiawan; Ibrahim; Ranto (CV. Multi Kreasi Media, 2022)
This study aims to describe the forms of patron-client relations and to find out the causes of the persistence of patron-client relations in legislative elections, especially in the electoral district I, Bangka Regency. The method used in this study is descriptive qualitative research method. Data collection was carried out using the interview method, researchers were required to interact with informants in a flexible and open manner in order to obtain all the data researchers needed. The theory used is Jamesscott's patron-client theory. The results of this study indicate that the patron-client relationship between legislative candidates and the community in electoral area I, Bangka Regency in 2019, is a reciprocal relationship between patrons and clients. The forms of this relationship include personal gifts, services and activities to the community, and buying votes. There are several factors that lead to the persistence of patron-client relations in the electoral district I, Bangka Regency, namely, the culture of money politics and the factor of weak supervision.